The clinical benefits of orthodontic treatment to pathologically migrated teeth: A systematic review - Gameiro Gustavo H.; Dalstra Michel; Cattaneo Paolo M. (Sciendo, 2019)
The present systematic review aimed to assess the evidence related to the periodontal benefits of orthodontic treatment of pathologically migrated teeth in combination with periodontal therapy with or without a regenerative procedure.